Effects of ionizing irradiation and interface backscatter on human mesenchymal stem cells cultured on titanium surfaces. (19th July 2019) - Printzell, Lisa; Reseland, Janne E.; Edin, Nina F. J.; Ellingsen, Jan E.
Abstract : Radiotherapy to the head and neck region negatively influences the osseointegration and survival of dental implants. The effects of cobalt 60 ( 60 Co) ionizing radiation and the impact of backscatter rays were investigated on human mesenchymal stem cells cultured on titanium surfaces. Bone marrow‐derived human mesenchymal stem cells were seeded on titanium (Ti), fluoride‐modified titanium (TiF), and tissue culture plastic. Cells were exposed to ionizing γ ‐radiation in single doses of 2, 6, or 10 Gy using a 60 Co source. Density and distribution of cells were evaluated using confocal laser‐scanning microscopy, 21 d post‐irradiation. Lactate dehydrogenase concentration and the levels of total protein and cytokines/chemokines were measured in the cell‐culture medium on days 1, 3, 7, 14, and 21 post‐irradiation. Unirradiated cells were used as the control. Irradiation had no effect on cell viability, collagen and actin expression, or cell distribution, but induced an initial increase in the secretion of interleukin (IL)‐6, IL‐8, monocyte chemotactic protein 1 (MCP‐1), and vascular endothelial growth factor (VEGF), followed by a decrease in secretion after 3 or 7 d. Irradiation resulted in secretion of a lower amount of all analytes examined compared with controls on day 21, irrespective of radiation dose and growth surface. Backscattering from titanium did not influence the cell response significantly, suggesting a clinical potential for achieving successful osseointegration of dental implants placed before radiotherapy.